E-COMMERCE BAJU JERSEYBOLAPADA NINE STUDIO BERBASIS WEB - IRFAN S, ANTON; Suhari, Yohanes (Information Technology and Telematics, 2018)
E-COMMERCE BAJU JERSEYBOLAPADA NINE STUDIO BERBASIS WEBShofwan, Dedi Lutfi1), Suhari, Yohanes2)1) Penulis,zeronineeight6@gmail.com2) Pembimbing, suhari_yohanes@yahoo.combstract- Nine Studio is a store that caters to the needs of the people of Semarang will be good quality soccer jersey goods affordable by people's purchasing power. Sales mechanisms that occur in Nine Studio currently still use a brochure that contains photos of goods and pamphlets in selling goods. Sales mechanism using brochures and pamphlets are still less than the maximum because of lack of information given about the detail of the goods offered, the sale of blogs also felt the customer is not good because the blog can not do transaction sales of goods and blogs Nine Studio currently only displays store information, address, and Nine Studio phone number only. Nine Studio sales process is still using conventional system that is customer who want to buy and find out new stuff from Nine Studio directly come to Nine Studio to find and choose goods to be purchased. System development method used in this research is Waterfall with stages of system start, system analysis, system design using UML and system implementation using PHP and MySQL.The result of this research is the creation of E-commerce Nine Studio web-based ball jersey dress that can assist the sales process, promotion process and facilitate long-distance transactions on Nine Studio.Keywords–Nine Studio, Baju Jersey Bola, PHP, MySQLDAFTAR PUSTAKAAchmad, Z, Fahrudin, T, Ramadhani, K.N, (2012), Aplikasi E-commerceBusana Hijab Menggunakan Symfony PHP framework (Studi Kasus : Zaza Shop), Skripsi, Politeknik Telkom BandungAditya, A.N, (2010), Jago PHP & MySQL Dalam Hitungan Menit, Dunia Komputer, BekasiHermawan, F., Risnandar, Fahrudin, T., (2010), Aplikasi E-Commerce Untuk Factory Outlet (Studi Kasus:Blackjack, Bandung), Skripsi, Politeknik Telkom BandungMeimaharani, R., Laily, D., (2014), Perancangan E-Commerce Goody Bag Spunbond Menggunakan QR Code Berbasis Web Responsif, Skripsi, Universitas Muria KudusPrasetyo, D.D, (2006), Administrasi Database Server MySQL, Elex Media Komputindo, Jakarta.Pratama, P.A.E, (2015), E-commerce, E-Business dan Mobile Commerce, Informatika, BandungPurdiantono, I., Wahid, A.K., (2013), Aplikasi CMS E-Commerce Penjualan Berbasis WAP Dengan Menggunakan PHP dan MySQL Di Toko Miulan Hijab Semarang, Skripsi, Universitas Dian Nuswantoro SemarangRejeki, R.S.A, Utomo, A.P., Susanti, S.S, (2011), Perancangan dan Pengaplikasian Sistem Penjualan pada “Distro Smith” Berbasis Ecommerce, Skripsi, Unisbank SemarangSutopo, A.H, (2006), Analisis dan Desain Berorientasi Objek, J & J Learning, Yogyakarta.Whitten, J.L. (2004), Metode Desain dan Analisa Sistem, Andi Offset, YogyakartaYakub. (2008), Sistem Basis Data Tutorial Konseptual, Graha Ilmu, Yogyakarta